Bi-Skew Lie (Jordan) Product on Factor Von Neumann Algebras (Contemporary Mathematics, 2024)
In this manuscript, we characterize the bijective mapping  between two von Neumann algebras  and  with dim ⩾ 1. The mapping Λ is to satisfy the following condition on the mixed bi-skew Lie (Jordan) product , for all , where the bi-skew Lie (Jordan) product is defined as  , and  . Specifically, we elaborate on the properties of the mapping Λ, establishing that it is additive, a∗-somorphism, and linear.
Keywords: von Neumann algebra; bi-skew Lie (Jordan) product; ∗-isomorphism